The Distribution Pattern And Marketing Efficiency Of Robusta Coffee At Tanggamus Regency - Apip Gunaldi Dalimunthe (Department of Management, Universitas Malikussaleh, Aceh Utara, Indonesia, 2021)
Coffee is one of the plantation comodities in Indonesia which has important economic value as a source of income for the country. Marketing is one of the most essential sub-systems to ensure the successfulness in agriculture. This research aims to know the pattern of marketing channels of robusta coffee and make analysis of efficiency level of robusta coffee marketing at Tanggamus Regency. The main problem in this research is the formed marketing channels will affect the final price of a robusta coffee product in the market. The method used in this research was descriptive analysis using snowball sampling technique with 68 farmers and 4 traders as respondents. The analaysis of marketing margin was used to know the gap of selling price in the level of producers and the selling price in the level of consumers. Farmer’s share was used to know the price for farmers. The result of this research shows that there are 3 patterns of marketing channel, they are: (1) Farmers to big collective traders to exporters, (2) Farmers to big traders to exporters, (3) Farmers to small collective traders to big traders to exporters. The efficient marketing channel is in the first channel because it has the smallest marketing margin whose margin is Rp. 1.520/Kg and the highest farmer’s share which reaches 93,42%.